DON'T DISCARD THOSE 3D GLASSES. - Milgrom, Harry (Science Education, 1956)
The article reflects on the role of glasses in shaping the flat images of the screen. It argues on the ability of the eyes and the brain to distinguish the varying depths in a three dimensional scene. It explains that in an ordinary light, vibrations that stimulate the eyes to see, occur in all directions at right angles to the incoming ray of light. It discusses results of the experiments on the nature of polarized light.